Measurement of (γ, p) reactions with ∆E − E telescope at Max-lab facility - Burdeinyi, D.; Brudvik, J.; Ganenko, V.; Hansen, K.; Fissum, K.; Isaksson, L.; Livingston, K.; Lundin, M.; Nilsson, B.; Schroder, B. (Вопросы атомной науки и техники, 2015)
The paper considers the results of experiments on the reactions ¹²C(γ, p)¹¹B and d(γ, p)n in the energy range of tagged photons 35...80 MeV. Demonstrated the possibility identification of protons by ΔE - E using CsI/SSD telescope. Using the spectra of the missing energy defined the values of differential cross sections of these reactions in the range of photon energies. The good agreement of the experimental results with the available data in the literature.